Self-compensating geopolymer utilizing nano-clay and chopped basalt fibers. (28th November 2022) - Li, Jingyao; Si, Jiwen; Luo, Feng; Zuo, Chuanxiao; Zhang, Peiping; Sun, Yanbin; Li, Wenqing; Miao, Shiding
Graphical abstract: Highlights: Self-compensating geopolymer was developed by using laponite and basalt fibers. The flexible basalt fibers was prepared via one-step drawing with PVA lubircation. The improved roughness and enhanced resistance to alkalis was obtained. Mechanism was found as hydrotalcite-like species formed in the geopolymer. Abstract: To eliminate the drying shrinkage as well as improve toughness of alkali activated geopolymer, the nano-sized laponite and chopped basalt fibers were utilized as additives to prepare self-compensating reinforced geopolymer. The magnesium-silicate laponite featured with gelable properties was found to influence geopolymerization in the slag/fly ash-based alkali system. This was validated by the new formation of hydration products as hydrotalcite-like phase (Ht). The release of Mg 2+ under activation promoted the participation of Al from the starting materials (slag and fly ash). Near-zero shrinkage was obtained at the dosage of laponite 4.0–5.0 wt% in the slag/fly ash-based geopolymetric mortars. The composite mortars exhibited excellent tensile-bond strength up to 5.7 MPa, and the low numbers pores of per unit area was achieved compared to other literatures. The flexural strength was improved by 51 % when the geopolymer was incorporated with flexible basalt fibers as modified with polyvinyl alcohol at dosage of 4.0 vol%.